2011
DOI: 10.1063/1.3643425
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching at manganite/manganite interfaces

Abstract: Electronic, lattice, and spin interactions at the interfaces between crystalline complex transition metal oxides can give rise to a wide range of functional electronic and magnetic phenomena not found in bulk. At hetero-interfaces, these interactions may be enhanced by combining oxides where the polarity changes at the interface. The physical structure between non-polar SrTiO3 and polar La1-xSrxMnO3(x=0.2) is investigated using high resolution synchrotron x-ray diffraction to directly determine the role of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…It has also been observed in oxide thin films [2] and insulators induced by strong electronelectron interaction [3,4]. This phenomenon has also been theoretically studied [5], and applied for the fabrication of memory cells [6][7][8][9]. Although the switching mechanism has not yet been completely understood, conducting filament model has been introduced for the resistive switching [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…It has also been observed in oxide thin films [2] and insulators induced by strong electronelectron interaction [3,4]. This phenomenon has also been theoretically studied [5], and applied for the fabrication of memory cells [6][7][8][9]. Although the switching mechanism has not yet been completely understood, conducting filament model has been introduced for the resistive switching [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…For manganites, only a few C-AFM studies have been published yet. [7][8][9][10] They focused mainly on the characterization of the different resistive states by I (V ) curves and the spatial appearance of resistively changed surface regions. The huge potential of this method for studying long-time evolution by successive scanning and, even more, in time-resolved spectroscopic modes has not been exploited extensively.…”
mentioning
confidence: 99%
“…CAFM measurements were recorded at vertical force set points ≤ 5 nN, and all current maps were recorded at a positive tip bias of 0.1 V. CAFM scanning over the sample surface, accompanied by switching on a nanometer-scale and simultaneous recording of the topography and current maps, has proven indispensable for microscopic study of memristive effects [73,[94][95][96][97][98]. Previously, we have shown that the surface of manganite epitaxial [73,98,99] and nanocolumnar [97] films initially exhibit a very high resistance state (HRS). It can be switched to a low resistive state (LRS) by applying a positive electric pulse voltage to the tip, U > 3 V, and back to HRS by applying a negative voltage pulse.…”
Section: Electric Field Effectmentioning
confidence: 99%